What Do Participation Fluctuations Tell Us About Labor Supply Elasticities? - Christian Haefke; Michael Reiter (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
In this paper we use information on the cyclical variation of labor market participation to learn about the aggregate labor supply elasticity. For this purpose, we extend the standard labor market matching model to allow for endogenous participation. A model that is calibrated to replicate the variability of unemployment and participation, and the negative correlation of unemployment and GDP, implies an aggregate labor supply elasticity along the extensive margin of around 0.3 for men and 0.5 for women. This is in line with recent micro-econometric estimates.
Keywords: E24; E32; J21; 330